2016
DOI: 10.7863/ultra.15.11057
|View full text |Cite
|
Sign up to set email alerts
|

Completion and Sensitivity of the Second‐Trimester Fetal Anatomic Survey in Obese Gravidas

Abstract: An increasing BMI category was associated with decreased completion of standard and detailed anatomic surveys by 20 weeks' estimated GA. Strategies to improve early visualization of the fetal head, chest, and abdomen in obese women should be investigated to promote anomaly detection and appropriate counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…Obstetric ultrasound is known to have limitations in this population (32,33). In one-quarter of mothers in this cohort, repeat midtrimester ultrasounds were required to complete the fetal anatomic survey because of poor visualization from maternal body habitus.…”
Section: Fetal Ultrasound Limitationsmentioning
confidence: 99%
“…Obstetric ultrasound is known to have limitations in this population (32,33). In one-quarter of mothers in this cohort, repeat midtrimester ultrasounds were required to complete the fetal anatomic survey because of poor visualization from maternal body habitus.…”
Section: Fetal Ultrasound Limitationsmentioning
confidence: 99%
“…However, from the midwife’s perspective, the intention to identify the sex during a routine ultrasound is secondary to the medical examination. Determining the sex is sometimes difficult, depending on the weight of the woman and the position of the fetus, and the examination may therefore demand more time ( 34 ). Many parents want to know the sex, but the caregiver is only allowed to disclose the sex of the expected child if the pregnant woman expresses such a wish.…”
Section: Discussionmentioning
confidence: 99%
“…One proposed mechanism is that high prepregnancy BMI decreases the likelihood of prenatal diagnosis of spina bifida via ultrasonography, decreases the likelihood of termination of pregnancy, and increases the probability that the liveborn case will be identified and included in the study (Peek & Nanan, 2009). This hypothesis is supported by studies that have found lower likelihood of prenatal diagnosis of birth defects among mothers with obesity, which makes the fetal anatomy difficult to visualize on ultrasound (Dashe, McIntire, & Twickler, 2009;Pasko, Wood, Jenkins, Owen, & Harper, 2016). This mechanism of selection bias is illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%